2019
DOI: 10.11648/j.ijbbmb.20190401.11
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilins: The Structure and Functions of an Important Peptidyl-prolyl Isomerase

Abstract: Cyclophilins are a subgroup of highly conserved protein family immunophilins which are peptidyl-prolyl isomerases that interconvert between the cis and trans positions. They can act as chaperones in maintaining conformational quality control of proteomes. They are structurally conserved throughout evolution and have been found in mammals, plants, insects, fungi, and bacteria. They share a common fold architecture consisting of 8 antiparallel beta sheets and two alpha helices that pack against the sheets. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…To determine whether BcCyp2 is a target of CsA, an immunosuppressive agent that binds to the cyclophilin and then inhibits calcineurin [ 11 , 17 ], we tested the sensitivity of the mutant strain Δ Bccyp2 to CsA. Our results demonstrated that conidial germination and hyphal development of the WT strain were dramatically suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine whether BcCyp2 is a target of CsA, an immunosuppressive agent that binds to the cyclophilin and then inhibits calcineurin [ 11 , 17 ], we tested the sensitivity of the mutant strain Δ Bccyp2 to CsA. Our results demonstrated that conidial germination and hyphal development of the WT strain were dramatically suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…Second, cyclophilins including BcCyp2 (this study) and Bcp1 [ 17 ] are necessary for CsA inhibition of infection-related development and virulence. In the presence of CsA, the formation of a CsA/cyclophilin complex targets calcineurin and prevents its activity in the regulation of fungal morphogenesis, e.g., hyphal branching/development, infection structure formation [ 11 , 12 , 17 , 21 , 29 ]. Our findings on the differential inhibition of hyphal development, infection structure formation, and host infection in the strains harboring or lacking BcCYP2 in the presence of CsA support this view ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cypa's efficiency can be compared to HSP90 in terms of its ability to keep the protein in its native form, which guarantees protection against loss of newly synthesized proteins. Peptidyl‐prolyl‐isomerase proteins anchor in proteins involved with splicing to assist in the proper folding of newly synthesized proteins during translation, to keep them organized by avoiding undesirable interactions (Idris et al, 2019).…”
Section: Discussionmentioning
confidence: 99%